(untitled) (ESMAT Magazine, 2022)
The main feature of the human being is its rationality. This condition guarantees you the title of being social, not only by the possibility of interaction, but by intrinsic necessity that man has to interact, either with other similar, or inanimate objects or their own madness, interacting with objects only by ideas it configured. This condition of being social is inherent to human beings. The Speech of Hatred as manifestation of thought is taken up before the public sphere that contains the public space of ideas as having a direct impact in the private sphere, especially in the free development of human personality, the virulent content features. In the face of Modern Theories of Justice, we seek to find a solution to this problem. To do so will be checking liberalism in the context of these theories and their relation to equality, particularly in the dimension of general principle, always observing the bias of freedom of expression within public and private spheres, in order to verify instruments that point to the imbalance or not in the public sphere contaminated by hate speech.